2006
DOI: 10.1162/neco.2006.18.3.569
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Analysis of the Influence of Fixational Instability on the Development of Thalamocortical Connectivity

Abstract: Under natural viev;.ring condition;:;, the physiological inotability of visual fixation keeps the projection of the stimulus on the retina in constant motion. After eye opcning 1 chronic exposure to a constantly moving retinal image might inf-luence the experience-dependent refinement of cell rcoponse characterioties. The rcoultf:i of previous modeling studies have f:iuggcstecl a contribution of fixational instability in the Hcbbian maturation of the noccptivc ficlcb of Vl simple cells (Rucci, Edelman, & \iVra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…As a consequence of this “ whitening ”, levels of correlation in our simulations were only determined by the spatial convolution of cell receptive fields, as during stimulation with spatial white noise. With the typical spatial characteristics of geniculate cells and V1 neurons, this convolution is very similar to the considered V1 kernel (Casile and Rucci, 2006). …”
Section: Resultsmentioning
confidence: 76%
See 4 more Smart Citations
“…As a consequence of this “ whitening ”, levels of correlation in our simulations were only determined by the spatial convolution of cell receptive fields, as during stimulation with spatial white noise. With the typical spatial characteristics of geniculate cells and V1 neurons, this convolution is very similar to the considered V1 kernel (Casile and Rucci, 2006). …”
Section: Resultsmentioning
confidence: 76%
“…In previous modeling studies, we suggested that fixational eye movements contribute to establishing a regime of neural activity compatible with the maturation of distinct ON and OFF subregions in the receptive fields of simple cells (Rucci, Edelman, and Wray, 2000; Rucci and Casile, 2004; Casile and Rucci, 2006). The results of the present study extend this hypothesis to LGN neurons with different response timings.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations